Los nombres de la hiel y bilis en castellano en la perspectiva diacrónica - Tilgner, Katarzyna (Neophilologica, 2018)
The aim of the research presented in the article is to determinate the cause of the coexistence of the three names of the bile / gall in Spanish and their semantic evolution through the centuries. The study is an attempt to explain this lexical abundance by invoking the similar richness in Latin.